Pharmacological Investigation of Fluoro-Gold Entry into Spinal Neurons. - Melanie Falgairolle; Michael J O'Donovan (PLoS ONE, 2015)
The fluorescent tracer Fluoro-Gold has been widely used to label neurons retrogradely. Here we show that Fluoro-Gold can also enter neurons through AMPA receptor endocytosis. We found that a 30 minute application of Fluoro-Gold to the isolated spinal cord labeled neurons under control conditions and in the presence of glutamatergic agonists including NMDA and AMPA. The labeling was abolished or greatly reduced by glutamatergic antagonists and the endocytic inhibitors Dynasore and dynamin inhibitory peptide. Whole cell recordings from spinal neurons exposed to extracellular AMPA revealed large inward currents that spontaneously decayed in the presence of the agonist but were maintained when a dynamin inhibitory peptide was included in the electrode. These findings suggest that Fluoro-Gold enters spinal neurons through AMPA-mediated receptor internalization. Drugs used to induce locomotor-like activity in the spinal cord also increased and decreased Fluoro-Gold labeling in a drug and lamina specific manner, indicating that AMPAR endocytosis is altered in the presence of the locomotor cocktail. Our findings suggest that endocytosis of Fluoro-Gold could potentially complicate the interpretation of experiments in which the tracer is used to label neurons retrogradely. Moreover, they also demonstrate that many drugs, including the locomotor cocktail, can modulate the number and/or the composition of AMPA receptors on spinal neurons and thereby affect network excitability.